Short-Term Response of Soil Microbial Community to Field Conversion from Dryland to Paddy under the Land Consolidation Process in North China - Xiaoxiao Li; Jing Ma; Yongjun Yang; Huping Hou; Gang-Jun Liu; Fu Chen (Agriculture, 2019)
Land consolidation of dryland-to-paddy conversion for improving tillage conditions and grain production capacity is widely implemented throughout the world. The conversion affects soil ecological stability, especially the most active soil microorganisms. However, the impacts of the dryland-to-paddy conversion has paid little attention in recent decades. In this study, a pot experiment was used to explore the responses of the microbial community and their interactions with soil properties after rice in the first season (five months). The results indicated that a significant decrease in the topsoil pH, organic matter content, nitrate nitrogen, and ammonical nitrogen, and an increase in soil electrical conductivity (EC) was observed (p < 0.05) after the dryland-to-paddy conversion. The richness and diversity of bacteria and fungi decreased in the short term. The composition of the soil microbial community and the soil microbial dominant bacteria had considerably changed after the conversion. Actinobacteria, Firmicutes, and Olpidiomycota were found to be highly sensitive to the dryland-to-paddy conversion. The soil microbial community structure had extremely significant positive correlations with soil pH, EC, organic matter, nitrate nitrogen, and ammonical nitrogen (p < 0.05). Microorganisms are the most important component of soil nutrient cycling. Converting a large area of dryland to paddy may lead to an imbalance in the soil carbonitride cycle and should be further examined in North China.